Biomass chitosan derived cobalt/nitrogen doped carbon nanotubes for the electrocatalytic oxygen reduction reaction. Issue 14 (13th March 2018) - Zhang, Yijie; Lu, Luhua; Zhang, Si; Lv, Zaozao; Yang, Dantong; Liu, Jinghai; Chen, Ying; Tian, Xiaocong; Jin, Hongyun; Song, Weiguo
Abstract : Biomass chitosan was used for the scalable synthesis of cobalt/nitrogen doped carbon nanotube composites with impressive oxygen reduction reaction activity and stability. Abstract : Carbon nanomaterials derived from biomass are considered as important sustainable energy carriers. In this study, we report an approach to synthesize cobalt/nitrogen doped carbon nanotubes (Co-NCNTs) for high oxygen reduction reaction (ORR) activity by cobalt catalyzed carbonization of biomass chitosan. It is found that the existence of cobalt results in the transition of graphene-like carbon nanosheets to tubular graphitic carbons. Moreover, a strong chemical bonding of cobalt with nitrogen and carbon in Co-NCNTs is found, which is important for enhancing the ORR activity. The Co-NCNT catalyst under optimized synthetic conditions displays attractive ORR activity superior to those of commercial Pt/C catalysts. Furthermore, the mechanism behind the enhanced ORR activity has also been studied. This study provides a feasible synthesis approach for the scalable production of biomass derived high performance carbon based ORR catalysts.